Investigations on the structural behavior of post-tensioned wind towers using a nonlinear 3d model - Chaves Neto, Francisco Guerreiro (2022)
Prestressed concrete has been used in place of steel in high rise towers of wind farms around the northeastern region of Brazil, in particular in Ceará S tate . Researches on the structural analysis of the these towers have sought a n alternative to make the analysis process more efficient by simplifying the problem modeling, which could lead to underestimating the applied loads or overestimating the structure strength, depending on the simplification chosen by the engineer. In either case, the preliminary design obtained from such simplified analysis may not be conservative for the problem, missing data that might be important to evaluate the strength and safety of the prestressed tower, such as localized stresses, cracking patterns, tendons behavior and free vibration mode shapes. The overall objective of this study is to offer a high fidelity model with shell, cable and solid elements, and to develop investigations on the structural behavior of prestressed concrete wind towers, providing parameter sensitivity information or to validate low fi delity models (beam models) that incorporate nonlinearities . The refined shell model is applied to an externally prestressed concrete tower with a tapered tube shape , 100 m high , using cable elements to represent the prestressed tendons and solid elements to simulate the foundation Structural analyses are performed using the DIANA software. Several aspects are investigated, such as wind model; load combin ations; element types; material and geometric nonlinearit ies; soil s tructure interaction; the effects of prestressed tendons detail s, such as the amount , distribution over the tower height and presence of deviators . Parametric studies have been done to study the sensitivity of the solution to various design parameters. The study has revealed important points to the design of wind towers and supplied contribution s to an improved beam element.